Butyrylcholinesterase—a potential plasma biomarker in manganese-induced neurobehavioral changes - Anjum, Adiba; Biswas, Sheta; Rahman, Mizanur; Rahman, Atiqur; Siddique, Abu Eabrahim; Karim, Yeasir; Aktar, Sharmin; Nikkon, Farjana; Haque, Azizul; Himeno, Seiichiro; Hossain, Khaled; Saud, Zahangir Alam (Environmental science and pollution research international, 2019)
Groundwater particularly drinking water contamination with metals has created an environmental disaster in Bangladesh. Manganese (Mn), an essential trace element, plays a key role in the development and function of the brain. Excess Mn exposure is reported to be associated with complex neurological disorders. Here, we have found a notably large extent of Mn above the permissive limit in the tube-well water of Rajshahi and Naogaon districts in Bangladesh. Higher levels of Mn in hair and nail samples, and a decreasing level of butyrylcholinesterase (BChE) activity were detected in plasma samples of the human subjects recruited from Naogaon district. Mn concentrations in water, hair, and nails were negatively correlated with the plasma BChE levels in Mn-exposed populations. To compare and validate these human studies, an animal model was used to determine the in vivo effects of Mn on neurobehavioral changes and blood BChE levels. In elevated plus maze, the time spent was significantly reduced in open arms and increased in closed arms of Mn-exposed mice compared to control group. The mean latency time to find the platform was declined significantly in control mice compared to Mn-treated group during 7 days in Morris water maze test, and Mn-exposed group also spent significantly less time in the desired quadrant as compared to the control group in probe trial. BChE activity was significantly reduced in Mn-exposed mice compared to control mice. Taken together, these results suggest that plasma BChE levels may serve as reliable biomarker of Mn-induced neurotoxicity related to behavioral changes.